Flexible n-type thermoelectric films based on Cu-doped Bi2Se3 nanoplate and Polyvinylidene Fluoride composite with decoupled Seebeck coefficient and electrical conductivity. (November 2015) - Dun, Chaochao; Hewitt, Corey A.; Huang, Huihui; Xu, Junwei; Zhou, Chongjian; Huang, Wenxiao; Cui, Yue; Zhou, Wei; Jiang, Qike; Carroll, David L.
Abstract: We report on the fabrication of flexible and freestanding n-type thermoelectric Cu intercalated Bi2 Se3 nanoplatelet/Polyvinylidene Fluoride (PVDF) composite films. The optimized power factor and figure of merit (ZT) of the Cu0.1 Bi2 Se3 nanoplatelet/PVDF composites are 103 μW m −1 K −2 and 0.10 at 290 K, respectively, which are one of the highest values for n-type thermoelectric films. The mechanism by which the Seebeck coefficient and electrical conductivity can be partially decoupled is explained in details: PVDF can not only grantee the robust and flexibility but also create a high trap-state by introducing the energy barrier at the organic/inorganic interface, thus a high level of Seebeck coefficient is maintained for the composite system while a remarkable improvement on electrical conductivity was achieved. The thermoelectric films show high mechanical durability with only a 13% decrease in performance after 5000 bending cycles (bending curvature 1/2 mm −1 ). The overall performance of the n-type thermoelectric films approaches the values required for efficient flexible thermoelectric power generators. Graphical abstract: Flexible and freestanding n-type thermoelectric Cu-intercalated Bi2 Se3 nanoplatelet/Polyvinylidene Fluoride composite films are fabricated. By introducing the energy barrier at the organic/inorganic interface, Cu0.1 Bi2 Se3 /PVDF thin film was found to possess considerably decreased electrical resistivity and lattice thermal conductivity, while maintain a relatively high Seebeck, leading to a high thermoelectric figure of merit (ZT=0.1) at 290 K. The superior flexibility and durability of the thermoelectric films make them suitable for applications in wearable electronics. Highlights: Flexible and free-standing n-type thermoelectric films with large power factor and ZT value. Enhanced electrical conductivity by intercalated Cu doping into the Bi2 Se3 nanoplates. Organic/inorganic interfaces induced decoupled Seebeck coefficient and electrical conductivity. Excellent mechanical durability with only 13% decrease in power after 5000 bending.